Simulation Integrated Management: A new type of simulation platform application for aerospace systems engineering. (February 2017) - Sun, Fuyu; Wang, Hua; Zhou, Jianping
In this paper, we propose a new simulation platform called SIM (Simulation Integrated Management) for analyzing parallel and distributed systems in the aerospace domain. This platform aims to test parallel and distributed architectures and applications. The main characteristics of SIM are its flexibility, scalability, and expandability. SIM has five management functions: model, experiment, distribution, operation, and node management functions. To improve the efficiency of project development, new sub-functionalities and assistive tools were designed for aerospace system simulation missions combined with SIM. Finally, a validation process and evaluation tests were developed and conducted, respectively, to evaluate the SIM simulator. SIM will become an excellent simulation platform with intelligence, versatility, and flexibility, laying the foundation for further validations of autonomy technology used in researches in the aerospace systems engineering domain.